?Are you a peer to peer pirate?? attitudes towards downloading movies and TV series through P2P networks - Teah, Min (School of Marketing, Curtin Business School, 2009)
This study sets out to investigate how collectivism and personal moral obligation may influence young consumers' attitudes towards the ethical stance of downloading of movies and TV series from the Internet and subsequent downloading behaviour. Data were collected using a convenience sampling method and 282 usable responses were used for analysis. The two factors were found to be significant predictors of attitudes, and in turn, attitudes is a significant predictor to intentions to download. Implications of the study and the corresponding recommendations are presented and discussed.